Eco-friendly synthesis of antibacterial zinc nanoparticles using Sesamum indicum L. extract - Sara Zafar; Asma Ashraf; Muhammad Umar Ijaz; Saima Muzammil; Muhammad Hussnain Siddique; Sidra Afzal; Rahat Andleeb; Khalid A. Al-Ghanim; Fahad Al-Misned; Zubair Ahmed; Shahid Mahboob (Journal of King Saud University: Science, 2020)
The present study was conducted to prepare cost effective and environment friendly zinc nanoparticles (Zn NPs) by using ZnSO4·7H2O and extract of sesame seeds. Zn NPs were characterized by using scanning electron microscope (SEM), Fourier-transform infrared spectroscopy (FTIR), X-Ray Diffraction and antibacterial potential was checked by using disc diffusion method. Solution colour turned yellow which ultimately confirmed the formation of Zn NPs and seed extract was used as a reducing agent. Crystalline size of the NPs was revealed by XRD spectra i.e. 9.07 nm. Functional groups were identified by the FTIR. SEM analysis given idea about the spherical shape of NPs. Antibacterial activity of the Zn NPs against different bacteria (S. pneumoniae, P. aeruginosa, E. coli and S. aureus) was measured by inhibition zone which ranged from 3.3 to 12.6 mm. Keywords: Zinc nanoparticles, Characterization, Antibacterial activity, FTIR, XRD